Lidar-relevant radiative properties of soot fractal aggregate ensembles. (January 2020) - Paulien, Lucas; Ceolato, Romain; Soucasse, Laurent; Enguehard, Franck; Soufiani, Anouar
Highlights: Lidar-relevant parameters (backscattering, extinction, lidar ratio, and depolarization ratio) are computed using MSTM for statistically representative ensembles of soot fractal aggregates. The monomer radius strongly influences all of the studied lidar relevant radiative properties The number of monomers per aggregate has also a strong effect on the lidar cross-sections, but has a limited impact on the lidar parameters such as the Lidar Ratio and the linear depolarization ratio. The aggregate fractal dimension has a weak impact on all lidar relevant radiative properties. Abstract: This study presents the averaged lidar-relevant radiative properties of numerically generated soot fractal aggregate ensembles. The radiative properties of these aggregates have been computed using the Superposition T-Matrix Method, with emphasis put on those that are most relevant to lidar application; the backscattering and extinction cross-sections, the Lidar Ratio and the Linear Depolarization Ratio. These lidar-relevant radiative properties have been computed over a broad spectrum, going from the ultraviolet to the near infrared, in order to address lidar instrument need for a priori knowledge in signal inversion procedures and measurement analysis. By averaging the computed radiative properties according to each set of morphological parameters, we obtain statistically representative results and we study the impacts of morphological changes on these lidar-relevant radiative properties. Our results show a strong impact of the primary particle radius on all considered radiative properties, while the number of primary particles induce significant variations on the cross-sections only. The fractal dimension, although being an essential morphological parameter, has a weak influences on the lidar-relevant radiative properties.